Estudo da estabilidade de maracujá (Passiflora edulis Sims f. flavicarpa degener) em pó, proveniente de cultivo orgânico. - Costa, Juliana Nascimento da (2012)
Passion fruit is a fruit which originates from Tropical America, is cultivated in countries with tropical and subtropical climates, and belongs to the Passifloracea family and Passiflora genus. Brazil is the largest producer of passion fruit in the world, and yellow or sour passion fruit is the most cultivated. Its production has focused on in natura consumption and industrialization. Among the methods of cultivation of passion fruit, the organic production system stands out. It is still incipient in Brazil, but there is great demand, especially in the European market, as it is becoming a common practice in order to combine food quality with environmental preservation. The yellow passion fruit is highly appreciated for the intense flavor and exotic aroma of this fruit, but it has high perishability which makes it difficult to increase the postharvest life and storage of in natura fruits. Considering the current trends in nutritional foods, which canbe prepared quickly their use in dehydrated form is an interesting alternative to reduce losses, add value to the product and provide other ways consume the fruit. Based on this information, the study aims to evaluate the stability of the passion fruit powder from organic cultivation, obtained by spray drying, during 360 days of storage at room temperature (±25ºC), characterizing it as to the physical-chemical, chemical and microbiological aspects, monitoring the quality of the product throughout its shelf life. The organic powder product was obtained from a fruit processing company, located in Ubajara, Ceara, north-east Brazil. After processing, the samples were taken to the Fruits and Vegetables Laboratory and to Food Microbiology Laboratory of DTA/CCA/UFC in Fortaleza, where they were kept at room temperature (±25°C) during the analytical procedures. The passion fruit powder was evaluated every 30 days during 360 days of storage, for the following parameters: pH, soluble solids, titratable acidity, SS/AT, water activity, moisture, ash, hygroscopicity, solubility, soluble sugars, reducers sugars, color coordinates L*, a*, b*, chroma (c*) and Hue (H*), total anthocyanins, yellow flavonoids, total extractable polyphenols, total chlorophyll, ascorbic acid and β-carotene. The passion fruit powder remained stable during 360 days of storage at room temperature (±25ºC), offering a great potential for use. It presented adequate retention of ascorbic acid, hygroscopicity desired, low water activity, acid pH stable, high levels of ash, sugars, total extractable polyphenols and satisfactory microbiological result so that the product was in optimum hygienic and sanitary condition, fit for human consumption.